2018
DOI: 10.1097/mph.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Investigation of Risk Factors of Oral Mucositis in a Pediatric Oncology Inpatient Population; a Prospective Study

Abstract: The prevalence of oral mucositis was 42.5% among inpatients and admission length was increased with increasing severity. Patient diagnosis, chemotherapy treatment block, day of chemotherapy cycle, and neutropenic status were shown to influence the risk of developing oral mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 28 publications
4
38
2
2
Order By: Relevance
“…Another study carried out in the HNL reference center demonstrated that children undergoing chemotherapy for hematological neoplasms developed OM more frequently [11]. Patients with hematological neoplasms were shown to have a seven-fold increased risk of presenting OM lesions when compared to those with solid or central nervous system tumors [6]. Despite this, in our study, there was no association between the occurrence of SOM and the type of tumor throughout the whole follow-up period.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Another study carried out in the HNL reference center demonstrated that children undergoing chemotherapy for hematological neoplasms developed OM more frequently [11]. Patients with hematological neoplasms were shown to have a seven-fold increased risk of presenting OM lesions when compared to those with solid or central nervous system tumors [6]. Despite this, in our study, there was no association between the occurrence of SOM and the type of tumor throughout the whole follow-up period.…”
Section: Discussioncontrasting
confidence: 78%
“…Unexpectedly, this study found no association between the use of MTX and the occurrence of SOM during ten weeks of treatment. Preventive oral care measures are known to mitigate the occurrence and progression of OM even in patients being administered high drug doses [6], which could partially explain the lack of association observed herein.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…구내염 환자 역시 마찬 가지로 중요한 구강간호대상이다. 구내염 발생률은 항암 치료를 받은 환아의 경우 32.6%에서 (Allen, Logan, Revesz, Keefe, & Gue, 2018) 방사선 치료를 받는 경 우는 최대 90%까지로 나타나 높은 편이며 (Bourhis et al, 2011), 관련된 치료를 받는 대상자에게는 삶의 질을 크게 위협하는 요인으로 지적되고 있다 (Harris, Eilers, Harriman, Cashavelly, & Maxwell, 2008). 특히, 가 시적인 구내염을 치유한 후에도 50%의 대상자는 오랜 기간 동안 구강 내 불편감을 호소한다는 보고에 근거할 때 (Rosenthal & Trotti, 2009) (Harris et al, 2008).…”
Section: 연구의 필요성unclassified
“…Patient diagnosis, chemotherapy treatment block, day of chemotherapy cycle, and neutropenic status have been shown to influence the risk of developing oral mucositis. [10] Pain, bleeding, ulceration, mouth dryness, change in taste, and malnutrition are generally observed in mucositis. The severity of oral mucositis leads to the tapering or postponement of chemotherapy and a longer period of hospitalization.…”
Section: Introductionmentioning
confidence: 99%